THE HEGEMONY OF THE DUTCH GOVERNMENT OVER THE POWER IN KARANGASEM BASED ON GEGURITAN1 LUNGA KA JEMBRANA WRITTEN BY A.A. ISTRI AGUNG - Puspawati, Luh Putu (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
Different types of values such as the values of love, dispute, sorrow, journey, genealogy, religiosity, education and so forth are narrated in a number of Balinese literary works. Unlike the other geguritans, Geguritan Lunga Ka Jembrana contains a highly unique value, namely the hegemony over a group of people taking place in 1908 when the Dutch government controlled the power in Karangasem through either authoritative measures or non-authoritative measures in such a way that what it did was considered justifiable. The geguritan entitled Lunga Ka Jembrana narrates the interference of the Dutch government with the legal power in the Karangasem Kingdom. The Dutch Colonial Government instructed Ratu Baginda Putri Holanda (the Dutch Queen), who then instructed Batavian Governor General and the Controller (the district officer of the colonial era) in Bali to exile the Karangasem King to Jembrana through the Cupel harbour. Finally, Ida Anak Agung Istri Agung narrated all the hegemonic measures and sufferings she underwent during the journey from Karangasem to Jembrana, where she stayed until 1913.